E-191 Influence of socioeconomic factors on the development of post-stroke depression in aneurysmal subarachnoid hemorrhage survivors. (23rd July 2022) - Lim, D; Abdi, C; George, L; Lim, K; Amruthur, M; Gonzalez, A; Prijoles, K; Haughn, H; Keen, J; Federico, E; Galang, C; Gulek, B; et al.
Abstract : Introduction/Proposal: The risk of developing depression based on the severity and location of injury and patient demographic factors is widely studied for ischemic stroke, but not well characterized for aneurysmal subarachnoid hemorrhage (aSAH) survivors. Furthermore, a direct relationship between socioeconomic factors and depression after aSAH has not been studied. The purpose of this study was to investigate the potential links between the development of depression and socioeconomic factors among survivors of aSAH. Materials/Methods: Data were retrospectively collected for 322 patients treated for aSAH at Harborview Medical Center (Seattle, WA) between 2014–2021. We excluded 133 patients due to inpatient mortality, previous history of depression, or previously prescribed psychotropic drugs. Demographic data and socioeconomic factors were collected ( Table 1 ). Multivariate logistic regression analyses were used with a primary outcome, development of new depression after aSAH. Results: Of the 189 patients that met inclusion criteria, 31 (16%) patients developed a new depressive disorder after aSAH. The average age was 57 years, and 25 (81%) patients were female. We collected socioeconomic factors from 180 of the 189 patients. A multivariate logistic regression analysis in these patients using 30 socioeconomic factors demonstrated reasonable predictive power, with an area under the curve score of 0.76. The mean predicted probability of developing depression in the subjects who did not develop depression (n=150) was 0.146 (SD=0.09), while the mean predicted probability among the cohort who did develop depression (n=30) was 0.25 (SD=0.12). A two-sample t-test between the predicted means of the two cohorts yielded a p-value of <0.001 and a t-statistic of 5.45. The most significant features in the logistic regression were female sex, employment at time of stroke, and a history of polysubstance abuse. Conclusion: The overall risk of developing a new depression disorder after aSAH was 16% in this retrospective study. The female sex was close to 4 times and substance use were six and half time more likely to develop new depressive symptoms; therefore, these risk factors should be considered when screening patients for depression after aSAH. Disclosures: D. Lim: None. C. Abdi: None. L. George: None. K. Lim: None. M. Amruthur: None. A. Gonzalez: None. K. Prijoles: None. H. Haughn: None. J. Keen: None. E. Federico: None. C. Galang: None. B. Gulek: None. D. Bass: None. R. Meyer: None. D. Coppel: None. C. Kelly: None. L. Kim: None. M. Levitt: None.